2013
DOI: 10.1177/0956797613504966
|View full text |Cite
|
Sign up to set email alerts
|

The New Statistics

Abstract: We need to make substantial changes to how we conduct research. First, in response to heightened concern that our published research literature is incomplete and untrustworthy, we need new requirements to ensure research integrity. These include prespecification of studies whenever possible, avoidance of selection and other inappropriate dataanalytic practices, complete reporting, and encouragement of replication. Second, in response to renewed recognition of the severe flaws of null-hypothesis significance te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
2,367
4
35

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,779 publications
(2,443 citation statements)
references
References 59 publications
37
2,367
4
35
Order By: Relevance
“…For the second part of this paper, we pooled the results of our models and examined them as part of meta‐analyses to provide a more robust test of the hypothesis that SES moderates the intention–behaviour gap, thus providing more precise estimates of effect sizes (see Cumming, 2014, for discussion and recommendation of this procedure). We conducted separate meta‐analyses for objective and self‐report measures of behaviours and different types of SES index (individual vs. area level).…”
Section: Methodsmentioning
confidence: 99%
“…For the second part of this paper, we pooled the results of our models and examined them as part of meta‐analyses to provide a more robust test of the hypothesis that SES moderates the intention–behaviour gap, thus providing more precise estimates of effect sizes (see Cumming, 2014, for discussion and recommendation of this procedure). We conducted separate meta‐analyses for objective and self‐report measures of behaviours and different types of SES index (individual vs. area level).…”
Section: Methodsmentioning
confidence: 99%
“…Only when the statistical power is at least 90% is a repeat experiment likely to return a similar P value, such that interpretation of P for a single experiment is reliable. In such cases, the effect is so clear that statistical inference is probably not necessary 25 .…”
Section: Box 1 Power Analysis and Repeatabilitymentioning
confidence: 99%
“…For example, it has been suggested that instead of basing statistical inferences on p -values, one should consider effect sizes or confidence intervals (e.g. Cumming, 2014; for Bayesian alternatives to these, see Kruschke and Liddell, in press). Although useful, here we decided to focus on BHT as this is a Bayesian alternative to NHST, which is commonly used in our field.…”
Section: Discussionmentioning
confidence: 99%